School of Medicine Professionalism Website (Out of Print) - Kathy Kreutzer; Carol Hampton; Chris Stephens; Jeanne Schlesinger; John Priestley; Brien White; Walter Lawrence; Heber Newsome (Association of American Medical Colleges, 2006)
Abstract This resource is a website that was developed to bring together learning material and information in the area of professionalism for students, housestaff, and faculty at medical schools. Features include standards and policies for medical schools, health systems, and medical centers; a description of a professionalism committee and the reporting mechanism for perceived unprofessional behavior; a section to support teaching and learning, including teaching cases, presentations, references, original research, and case studies; and news about local events related to professionalism including ceremonies, awards and other opportunities for recognition, and presentations. Using a logic model, we evaluated this effort by linking activities, outputs, outcomes, and impacts. Outputs and outcomes include dissemination of professionalism policies and standards; a "standard of the month" reminder; and three Group on Education Affairs regional meeting poster presentations. This website has also been included in faculty development for graduate medical educators program directors and undergraduate medical education course directors and in departmental grand rounds. The website does not remain static and is continuously updated and maintained in order to be useful. There has been a very positive reaction to making all of these resources available in one place. This website is an ongoing team effort by the admissions, undergraduate education, housestaff education, faculty, instructional development, and student activities offices at the Virginia Commonwealth University Medical Center and the Hunter Holmes McGuire Veterans Administration Medical Center.